The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/brainsci12010005
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Training with Neurofeedback Using NIRS Improved Cognitive Functions in Young Adults: Evidence from a Randomized Controlled Trial

Abstract: (1) Background: A previous study has shown that cognitive training with neurofeedback (CT-NF) using down-regulation improves cognitive functions in young adults. Neurofeedback has two strategies for manipulating brain activity (down-regulation and upregulation). However, the benefit of CT-NF with the upregulation of cognitive functions is still unknown. In this study, we investigated whether the upregulation of CT-NF improves a wide range of cognitive functions compared to cognitive training alone. (2) Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(36 citation statements)
references
References 38 publications
(89 reference statements)
2
32
0
Order By: Relevance
“…We used the permutation ANCOVA test because it is suitable for small sample analysis and is freely distributed. Therefore, the permutation ANCOVA test is suitable and sufficiently powered for present study ( Kulason et al, 2018 ; Nouchi et al, 2020b , 2022 ). The changes in scores in each group (AC training group, A training group, C training group, and active control group) were the dependent variables.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We used the permutation ANCOVA test because it is suitable for small sample analysis and is freely distributed. Therefore, the permutation ANCOVA test is suitable and sufficiently powered for present study ( Kulason et al, 2018 ; Nouchi et al, 2020b , 2022 ). The changes in scores in each group (AC training group, A training group, C training group, and active control group) were the dependent variables.…”
Section: Discussionmentioning
confidence: 99%
“…All training groups performed three cognitive training tasks (short-term memory, working memory, and attention training tasks) with intensity level controlled audio stimuli ( Figure 2 ). The short-term, working memory, and attention training tasks were developed based on our previous cognitive training studies ( Nouchi et al, 2016a , 2019 , 2020a , 2021 , 2022 ; Takeuchi et al, 2020 ). Each cognitive training task had 4 task difficulty levels as a cognitive training factor [from level 1 (easy) to level 4 (difficult)].…”
Section: Experimental Methodsmentioning
confidence: 99%
“…It should be important to consider whether the intervention period of the included studies was sufficient to evaluate improvements in cognitive function. Previous systematic review and meta-analysis for non-pharmacological interventions such as cognitive training, exercise, nutrition revealed that previous studies used the similar intervention periods (from 4 to 12 weeks) [ 25 , 69 , 70 , 71 , 72 ]. The short-term intervention was able to improve cognitive functions in older adults with and without dementia.…”
Section: Discussionmentioning
confidence: 99%
“…In the typical CTNF, participants were asked to perform CT while maintaining greater brain activities. Several studies have reported that CTNF has a positive effect on cognitive functions [ 26 , 27 ]. For example, previous studies using NIRS reported that the CTNF showed greater beneficial effects on working memory, long-term memory, attention, and executive functions compared with CT alone in healthy adults [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported that CTNF has a positive effect on cognitive functions [ 26 , 27 ]. For example, previous studies using NIRS reported that the CTNF showed greater beneficial effects on working memory, long-term memory, attention, and executive functions compared with CT alone in healthy adults [ 27 , 28 ]. These studies suggest that CTNF has a more positive impact on cognitive function than single domain training (e.g., CT or neurofeedback alone).…”
Section: Introductionmentioning
confidence: 99%